PEMBUATAN CARICA FRUIT LEATHER DENGAN SUHU PENGERINGAN YANG BERBEDA - Akmal Sugiyarto; Ilham Fajri (JURNAL PARIWISATA VOKASI, 2021)
This study aims to determine the right temperature in the manufacture of Carica fruit leather which will produce the best organoleptic test results and is favored by panelists and also as a food diversification made from Carica fruit can minimize the value of post-harvest loss by processing it into fruit leather can increase the economic value of the Carica fruit and also determine the acceptance of Carica fruit leather products to tourists who visit the tourist area of Dieng and the citizens of Dieng. The collection method used is the experimental method. Data collection techniques were carried out using product experiments, distributing questionnaires, and observing. While the data analysis technique using a hedonic scale. Based on the results of the study, it can be seen that professional panelists prefer Carica fruit leather with a temperature of 70oC. Similar to the professional panelists, the consumer panelists for Carica fruit leather with a temperature of 70oC were superior with the criteria of Carica fruit aroma, sweet and slightly sour taste, slightly brownish yellow color, and slightly rough, thin & elastic texture; then the selling price that the author gets with a profit of Rp.212,050, - is Rp.899.540,-per 100 pcs, then the selling price of Carica fruit leather per pc unit is Rp. 8.955,-; and acceptance of Carica fruit leather products are included in the "Accepted" category. Problems in research: 1) What is the taste of fruit leather made from Carica fruit with different drying temperatures? 2) How to calculate the selling price of fruit leather made from Carica fruit with different drying temperatures? 3) How is the potential for consumer acceptance of fruit leather made from Carica fruit with different drying temperatures?. Suggestions given for problem-solving are: 1) Carica fruit leather product packaging can be improved again to make it more attractive, efficient and also increase its selling value; 2) The shape of the Carica fruit leather product can still be reduced to make it easier to eat; 3) If viewed from the aspect of the cost of Carica fruit leather products, it is still too cheap, so it can still be developed in terms of shape, packaging, and others.